Institutional capacity, faculty capability, and research productivity in higher education institutions: A moderated mediation model - Malaga, Ronora Sevilla (Edelweiss Applied Science and Technology, 2025)
A strong research culture serves as a catalyst for the fulfillment of educational institutions’ vision and mission. Predicated on the positivistic paradigm, the paper determined the role of research capability as a mediator in the relationship between institutional capacity and productivity in the research of HEIs’ faculty in one province in the central Philippines. The paper employed descriptive and moderated mediation analyses utilizing the Research Capacity, Capability, and Productivity Metrics (RCCPM) for data collection. Forty-three HEIs and 356 faculty respondents participated in the study. Findings revealed that the faculty perceived HEIs’ institutional capacity in research and their capability in research as moderate. Conversely, research production was extremely low. Applying the mediation analysis, institutional capacity influences faculty capability in research, which in turn impacts research productivity. Based on the findings, HEIs, together with allied agencies, need to boost faculty knowledge and skills in research to ensure improved productivity in research.